(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective:-Hepatitis B is noteworthy medical issues that may include the late continuation of liver cirrhosis and hepatocellular carcinoma. The present study aimed to know the seroprevalence of hepatitis B Virus in Meerut with different clinical conditions. Methods: The studyconducted on 4927 patients in Meerut, India, which was performed in central research center labortory of Microbiology at netaji subhash Chandra Bose Medical College and Hospital Between January 2013 to April 2017 The sera were separated and screened for HBsAg byimmune-chromatographic card test then HBsAg positive serum sampleswere tested again for HBsAg using ELISA kit. Positive samples for HBsAgwere tested for HBeAg ELISA kit. Results: In 245 positive cases 118 (48.16 %) were male and 127 (51.84%) were female. The seroprevalence rate of HBV was 4.97% in Meerut, India. Age group21–30 was the highest seroprevalence (7.46%) when compaired to other age group. Of the 245 HBsAg Positive case 55 (1.12%) were HBeAg positive. 20 were male, Highest HBeAg positive male were found in 21- 30age group. Out of 55 HBeAg cases, 35 were female and 92 female were negative for HBeAg, this was stastically significant (P< 0.039) by using Z test. Conclusions: The study uncovered that the seroprevalence of HBV was alarmingly higher in such a populace, which presumably mirrors a high foundation predominance of HBV contaminations ought to be mulled over and Implementation of group based preventive measures and enhanced procedures for safe blood supply may demonstrate valuable to diminish the seroprevalence Bangladesh Journal of Medical Science Vol.18(2) 2019 p.329-333